LAJU PINDAH PANAS SECARA KONDUKSI DAN PENGUAPAN AIR SELAMA PROSES PENGERINGAN GABAH MENGGUNAKAN CABINET DRYER - Sasmita Sasmita; Jamaluddin P Jamaluddin P; Husain Syam (Jurnal Pendidikan Teknologi Pertanian, 2018)
The purpose of this research is to know the mechanism of heat transfer and water evaporation grain water during drying process using hot air as heat conducting media. This experiment is an experiment consisting of two variables, namely variable A is temperature with 3 level 50o, 60o and 70oC and variable B is drying time with 3 level 160, 170, and 180 minutes. The sample was wet grain with initial moisture content of 20.51% dried using a cabinet dryer. To determine the temperature changes that occur then the drying process is done by measuring the temperature of the environment / air and grain temperature using thermocouple. Before and after drying the water content is measured to determine the change of grain water level of each treatment used. The results showed that the higher temperature and the longer drying is used the higher heat transfer rate, the greater the evaporation of water, causing the grain water content to decrease